Analysis of the Influence Between Study Plan, Locus of Control Learning Achievement at BSM 1 High School in 2024 - Roy, Andri (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
All learning objects at the high school level should be a concern. Theoretical and practical studies are balanced. Investigation and understanding at the theoretical and practical levels provide an understanding of the various materials of all subjects provided by the school to students. Improved student abilities demonstrated through learning outcomes can certainly be used to adapt and innovate to meet economic, environmental and social needs in an ever-evolving world. This includes addressing the global challenges of climate change and energy constraints by designing processes to maximize the efficient use of the earth's limited resources. Some lessons are practical learning. Learners are trained to conduct simple qualitative and quantitative research both individually and collaboratively on a range of real-world phenomena. Learners learn to find problems, make hypotheses, design simple experiments, conduct experiments, analyze data, draw conclusions and communicate the results of experiments both in writing and orally.